Voices from the moon : Apollo astronauts describe their lunar experiences - Chaikin, Andrew, 1956-; Kohl, Victoria (New York : Viking Studio ; London : Turnaround [distributor], 2009)
Provides recollections from Apollo astronauts and a collection of photographs that document the history of the Apollo space program.
Before -- Preparing -- Outward bound -- Another world -- Landing -- On the surface -- Solo -- Homeworld -- Apollo 13 -- Aftermath -- Remembering -- Spirit of Apollo.
Keywords: Project Apollo (U.S.) -- History; Space flight to the moon -- History; Space flight to the moon -- Quotations, maxims, etc